AKT serine/threonine kinase 2-mediated phosphorylation of fascin threonine 403 regulates esophageal cancer progression. (April 2022) - Zhang, Zhi-Da; Wen, Bing; Li, Da-Jia; Deng, Dan-Xia; Wu, Xiao-Dong; Cheng, Yin-Wei; Liao, Lian-Di; Long, Lin; Dong, Geng; Xu, Li-Yan; Li, En-Min
Abstract: Fascin is the main actin-bundling protein in filopodia and is highly expressed in metastatic tumor cells. The overexpression of Fascin has been associated with poor clinical prognosis and metastatic progression. Post-translational modifications of Fascin, such as phosphorylation, can affect the proliferation and invasion of tumor cells by regulating the actin-bundling activity of Fascin. However, the phosphorylation sites of Fascin and their corresponding kinases require further exploration. In the current study, we identified novel phosphorylation of Fascin Threonine 403 (Fascin-T403) mediated by AKT serine/threonine kinase 2 (AKT2), which was studied using mass spectrometry data from esophageal cancer tissues (iProX database: IPX0002501000). A molecular dynamics simulation revealed that Fascin-Threonine 403 phosphorylation (Fascin-T403D) had a distinct spatial structure and correlation of amino acid residues, which was different from that of the wild type (Fascin-WT). Low-speed centrifugation assay results showed that Fascin-T403D affected actin cross-linking. To investigate whether Fascin-T403D affected the function of esophageal cancer cells, either Fascin-WT or Fascin-T403D were rescued in Fascin-knockout or siRNA cell lines. We observed that Fascin-T403D could suppress the biological behavior of esophageal cancer cells, including filopodia formation, cell proliferation, and migration. Co-immunoprecipitation (Co-IP) and Duolink in situ proximity ligation assay (PLA) were performed to measure the interaction between Fascin and AKT2. Using in vitro and in vivo kinase assays, we confirmed that AKT2, but not AKT1 or AKT3, is an upstream kinase of Fascin Threonine 403. Taken together, the AKT2-catalyzed phosphorylation of Fascin Threonine 403 suppressed esophageal cancer cell behavior, actin-bundling activity, and filopodia formation. Graphical Abstract: ga1 Highlights: Fascin was highly expressed in human cancers and correlated with a poor prognosis. Fascin threonine 403 phosphorylation regulates esophageal cancer progression. Fascin is a novel effector of AKT serine/threonine kinase 2.